Resolução NTC/PRGO nº 3, de 13 de junho de 2022 - Marcello Santiago Wolff; Lea Batista de Oliveira Moreira Lima; Mariane Guimaraes de Mello Oliveira; Viviane Vieira de Araujo; Ailton Benedito de Souza (DMPF-e, Brasília, DF, 20 jun. 2022 Caderno Administrativo, p. 11., 2022)
Altera a Resolução NTC-PRGO nº 2, de 2 de junho de 2022.